If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9m + -3(m + -6) = 2(m + 1) Reorder the terms: 9m + -3(-6 + m) = 2(m + 1) 9m + (-6 * -3 + m * -3) = 2(m + 1) 9m + (18 + -3m) = 2(m + 1) Reorder the terms: 18 + 9m + -3m = 2(m + 1) Combine like terms: 9m + -3m = 6m 18 + 6m = 2(m + 1) Reorder the terms: 18 + 6m = 2(1 + m) 18 + 6m = (1 * 2 + m * 2) 18 + 6m = (2 + 2m) Solving 18 + 6m = 2 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 18 + 6m + -2m = 2 + 2m + -2m Combine like terms: 6m + -2m = 4m 18 + 4m = 2 + 2m + -2m Combine like terms: 2m + -2m = 0 18 + 4m = 2 + 0 18 + 4m = 2 Add '-18' to each side of the equation. 18 + -18 + 4m = 2 + -18 Combine like terms: 18 + -18 = 0 0 + 4m = 2 + -18 4m = 2 + -18 Combine like terms: 2 + -18 = -16 4m = -16 Divide each side by '4'. m = -4 Simplifying m = -4
| 10d-45=3(b-15) | | 10h^2-2h-5=0 | | 4o+16=2o-14 | | 7x-4+5x+8=180 | | 15x^3+24x^2+9x=0 | | y=45-8 | | X+x=124 | | 2x=60-3y | | -4y+2x=9 | | 4p+3=18 | | -2+12= | | x+(x+3)(x-3)=3+x(x+2) | | 4x+9=4x+8 | | 4x^2-18x+14=0 | | 2x^4+2x^3-49x^2-50x-25=0 | | 46-3+x+x+x+x+x+x+x-15=41 | | 6x^2+41xy-30y^2= | | 3x+(-6)=8+(-4x) | | 20p-1.25=117 | | 6x^2+17u-10=0 | | 14=3k+27-10k | | 32.50t+3.30t+5.90=220.70 | | -15=-7+2u | | 3x^2+2+3=0 | | x^2-9x=0.2x^2+6x | | 3x^2-qx-14=0 | | 3x^2+x=(x+5)x | | 32.50t+3.30+5.90=220.70 | | 24x-120=135 | | -1.7y=-34 | | -2x+4=36 | | 1.5x+8=3+2x |